Biological and Pharmacological Activities of Carvacrol and Carvacrol Bearing Essential Oils - Baser, K.H.C.
Oregano essential oils obtained from the genera Origanum, Thymus, Coridothymus, Thymbra, Satureja and Lippia are rich in carvacrol, a monoterpenic phenol isomeric with thymol. Turkey is the biggest exporter of oregano herb and oil to the world markets. Oregano is mainly used in food, spice and pharmaceutical industries. Carvacrol is responsible for the biological activities of oregano. Many diverse activities of carvacrol such as antimicrobial, antitumor, antimutagenic, antigenotoxic, analgesic, antispasmodic, antiinflammatory, angiogenic, antiparasitic, antiplatelet, AChe inhibitory, antielastase, insecticidal, antihepatotoxic and hepatoprotective activities and uses such as feed additive, in honeybee breeding and in gastrointestinal ailments have been shown. This paper highlights these activities and attempts to explain the possible in vivo mechanism of action of carvacrol.
Keywords: CARVACROL; OREGANO; BIOLOGICAL ACTIVITY; ESSENTIAL OIL; MONOTERPENIC PHENOLS